Juridical Analysis Of The Application For Cancellation Of The Arbitration Award Of The Indonesian National Arbitration Board (Decision Study Number 531 / Pdt.Sus-Arb/2023 / PN Bks) - Hasbi, Mhd; Safnul, Dody (Universitas Dharmawangsa, 2025)
This paper examines the juridical application for cancellation of the arbitration award of the Indonesian National Arbitration Board (BANI) Surabaya in the case between PT Adhi Persada Properti against Haryono Soebagio and Budi Said. This dispute stems from default in the implementation of the deed of binding agreement of sale and purchase (PPJB) No. 008/2017, which was then terminated through the BANI Surabaya Arbitration forum. The applicant filed a cancellation of the arbitration award under Articles 70 and 71 of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution, on the grounds of alleged fraud and violation of the principle of due process of law. This study uses normative juridical methods, with a legal and conceptual approach, and examines the relevance of this decision to the protection of legal certainty in arbitration practice in Indonesia.